Elementary school counseling : a commitment to caring and community building - Worzbyt, John C. (Brunner-Routledge, 2003)
Innovative, practical and packed with ideas, this dynamic resource revolutionizes elementary school counseling programs and their mission to create caring school communities that support a climate for learning and a commitment to developing human potential. Over 200 new, fun and easy-to-use activities, suggestions, and helpful resources support a blueprint for success in creating and managing comprehensive, developmental, and collaborative elementary school counseling programs that will foster s.